Caching behaviour by red squirrels may contribute to food conditioning of grizzly bears - Put, Julia Elizabeth; Put, Laurens; St. Clair, Colleen Cassady (Nature Conservation, 2017)
We describe an interspecific relationship wherein grizzly bears (Ursus arctos horribilis) appear to seek out and consume agricultural seeds concentrated in the middens of red squirrels (Tamiasciurus hudsonicus), which had collected and cached spilled grain from a railway. We studied this interaction by estimating squirrel density, midden density and contents, and bear activity along paired transects that were near (within 50 m) or far (200 m) from the railway. Relative to far ones, near transects had 2.4 times more squirrel sightings, but similar numbers of squirrel middens. Among 15 middens in which agricultural products were found, 14 were near the rail and 4 subsequently exhibited evidence of bear digging. Remote cameras confirmed the presence of squirrels on the rail and bears excavating middens. We speculate that obtaining grain from squirrel middens encourages bears to seek grain on the railway, potentially contributing to their rising risk of collisions with trains.